MiRNA-3Age: a microRNA-based biological age model and its modulation by lifestyle and nutrition - Schneider, Jana; Preyer, Clara; Steil, Marie; Biazid, Maruan; Pointner, Angelika; Haslberger, Alexander G.; Hippe, Berit (Frontiers in Nutrition, 2025)
IntroductionThe extension of human longevity has intensified the search for biomarkers that capture not only chronological age but also biological aging and functional healthspan. Among molecular candidates, microRNAs (miRNAs) have emerged as promising regulators and indicators of aging-related processes. In this pilot study, we explored whether selected circulating miRNAs could serve as potential biomarkers of biological age and lifestyle-associated aging dynamics.MethodsBased on current literature, we focused on three miRNAs—miR-24, miR-21, and miR-155—previously linked to inflammation, senescence, and metabolic regulation. Capillary blood samples from a heterogeneous adult cohort were analyzed using quantitative PCR. ΔCt values were integrated into a composite “miRNA-3Age” model through multivariate regression analysis to estimate biological age. Associations between lifestyle variables (diet, exercise, stress, and smoking) and miRNA-based biological age were examined.ResultsThe miRNA-3Age model predicted biological age with moderate correlation to chronological age and revealed variability consistent with individual health profiles. Participants with favorable lifestyle factors (e.g., frequent consumption of fish, whole grains, and green tea; regular exercise) tended to exhibit lower miRNA-3Age estimates, whereas stress and smoking were associated with higher predicted biological age.DiscussionOur exploratory data suggest that integrating multiple miRNA signals may enhance the sensitivity of biological age estimation compared to single-biomarker approaches. However, variability within the small sample highlights the need for larger, longitudinal datasets to confirm predictive validity and to disentangle causal links between lifestyle, miRNA expression, and aging biology.ConclusionThis pilot study supports the feasibility of miRNA-based biological age modeling and identifies miR-24, miR-21, and miR-155 as promising components of a composite biomarker framework. The miRNA-3Age model provides a preliminary step toward a scalable, lifestyle-sensitive aging metric that warrants validation in diverse populations.